Communication with multiple senders: An experiment. Issue 1 (March 2016) - Vespa, Emanuel; Wilson, Alistair J.
Abstract : We implement multi‐sender cheap talk in the laboratory. While full‐information transmission is not theoretically feasible in the standard one‐sender–one‐ dimension model, in this setting with more senders and dimensions, full revelation is generically a robust equilibrium outcome. Our experimental results indicate that fully revealing outcomes are selected in particular settings, but that partial‐information transmission is the norm. We uncover a number of behavioral patterns: On the one hand, senders follow exaggeration strategies, qualitatively similar to those predicted by a special case for the fully revealing equilibrium. Receivers, on the other hand, follow differing heuristics depending on the senders' biases, which are not always sequentially rational. When full revelation is observed it can be explained as the intersection of the receiver heuristics with the equilibrium response.